Evaluation of the microscopic observation drug susceptibility assay for detection of Mycobacterium tuberculosis resistance to pyrazinamide - Ghiraldi, L. D.; Campanerut, P. A. Z.; Spositto, F. L. E.; Sato, D. N.; Leite, Clarice Queico Fujimura [UNESP]; Hirata, M.; Hirata, R. D. C.; Cardoso, R. F. (Wiley-Blackwell, 2011)
The microscopic observation drug susceptibility assay (MODS) was evaluated to determine susceptibility to pyrazinamide in Mycobacterium tuberculosis, and compared with the broth microdilution method (BMM), absolute concentration method (ACM), and pyrazinamidase (PZase) determination. We tested 34 M. tuberculosis clinical isolates (24 sensitive and eight resistant to pyrazinamide) and the control strains M. tuberculosis H37Rv (ATCC 27294) and Mycobacterium bovis AN5. The MODS, BMM, ACM and PZase determination provided results in average times of 6, 18, 28 and 7 days, respectively. All methods showed excellent sensitivity and specificity (p <0.05). of the methods studied, the MODS proved to be faster, efficient, inexpensive, and easy to perform. However, additional studies evaluating the MODS in differentiating pyrazinamide-resistant and pyrazinamide-susceptible M. tuberculosis must be conducted with a larger number of clinical isolates.
Keywords: Microscopic observation drug susceptibility assay (MODS); pyrazinamide; resistance; susceptibility testing; tuberculosis